Thermal neutron detection enhancement by 10B implantation in silicon carbide sensor. Issue 1693 (14th July 2014) - Vervisch, Vanessa; Issa, Fatima; Biondo, Stéphane; Ottaviani, Laurent; Vervisch, Wilfried; Szalkai, Dora; Vermeeren, Ludo; Klix, Axel; Hallen, Anders; Kuznetsov, Andrej; Lazar, Mihai; Lyoussi, Abdallah
ABSTRACT: The purpose of this paper is to propose the enhancement of device detectors based on p-n junction in 4H-SiC for nuclear instrumentation. Particular emphasis is placed on the interest on using Boron isotope 10 as a Neutron Converter Layer in order to detect thermal neutrons. Here, we present the main results obtained during several irradiation tests performed in the Belgian Reactor 1 (BR1). We show the capability of our detectors by means of first results of the detector response at different reverse voltage biases and at different reactor power.